Socio-Economic Profile Of Coastal Fishing Communities: A Case Study On Fishermen - Participants From Azam Tani Programme And Social Welfare Development Scheme(SPKR), In Terengganu, Malaysia - Norizan, Abdul Ghani; Dara Aisyah H.M, Ali Puteh (2016)
Poverty among the fishermen is still one of the country’s main problems. Various development projects in the fisheries sector have been carried out, to address these issues, but in general, the plan was found to be less than successful and less effective. Therefore, the government launched various programmes such as Social Welfare Development Scheme (SPKR) in 2007 and Azam Tani program in 2010. These two programmes are public related and implemented in order to help increase the poor and unfortunates’ source of income. In order to develop the fisheries sector, the Fisheries Development Authority of Malaysia (LKIM) also works to ensure fishermen benefit from the programme in order to improve their socio-economic status. This study aims to assess the socio-economic aspects of coastal fishermen who receive funds and help from the programme under LKIM. Data were collected through several ways, namely; in depth interviews with the programme participants, interviews with key informants from LKIM, and through focus group discussion between fishermen (participants of Azam Tani Programme), SPKR and the programme organiser. The findings showed that fishermen living in areas where both SPKR and Azam Tani programmes took place, saw no changes in the participants’ socio-economic profiles as it was still low. Fishermen need moral support from agencies involved to boost their socio-economic status. They also need assistance in the form of health facilities, food, education, religion and future life guarantees. This assistance will contribute to the improvement of their socio-economic status. In general, fishing becomes a career due to poverty, where most fishermen have only completed primary school, have no skills, no extra income, and their wives only work as housewives. The level of income before and after being provided the funds and assistance has not changed their status, but the rates of spending were found to be greater than the monthly income. The study found that most participants have no savings, the fishermen’s needs are unparallel with the assistance provided in the programme, the agencies involved offer inefficient management and no subsidy or social guarantees are provided to the fishermen and these factors, faced by the fishermen participants, are affecting their learning process through the program which is, up to now, still unfinished. Thus, well planned and controlled improvements that suit the needs of fishermen need to be implemented so that the poverty issue of fishermen can be overcome in the future